Impact, Position, Prospects and Challenges of Online Education in Teachers Professional Development in Karnali Province, Nepal - Singh, Kamal Bahadur; Yadav, B.P. (A Bi-annual South Asian Journal of Research & Innovation, 2024)
In the province of Karnali in Nepal, there are a number of potential and problems for distance learning and online schooling. We conducted an extensive examination of the relevant literature, and as a result, we were able to identify critical elements that would improve online education in the Karnali area of Nepal. There are a number of challenges that are preventing the expansion of the industry, including inadequate digital infrastructure, trust issues, and the terminology that is utilized in online education. Nepal’s Karnali region has seen a surge in the number of people using the internet in recent years, prompting the country’s education system to investigate potential new avenues for growth.